PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KOMITMEN KARYAWAN DAN KINERJA PERUSAHAAN - Brahmasari, Ida Ayu (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2008)
Change and competition are inevitable for every business. In order to survive the change and competition, every business must be able to adapt its external environment as well as to integrate its internal enivironment by creating an organizational culture. Organization culture affects every organization aspects dan a number of outcomes such as productivity, performance, commitment, and ethical behaviors. This research aims to examine and analyze the influence of organization culture and employees’ motivation on employees’commitment and company’s performance. Data from 105 respondents were collected and analyzed using Structural Equation Modelling analysis. Result of this study proved that organization culture and employees’ motivation have significant influences on employees’ commitments and company’s performance. Employees’ commitments also has significant influence on company’s performance. However, both organization culture and employees’ motivation influences on company’s performance are negative. Key words: organization culture, motivation, commitment, performance